Les réformes agraires en Afghanistan,de la fin de la monarchie à la chute des talibans - Pierre Centlivres; Micheline Centlivres-Demont (Revue des Mondes Musulmans et de la Méditerranée)
The authors first describe the situation of peasants and agricultural production methods in Afghanistan on the eve of the 1978 coup d'état. They then describe the agrarian reforms put in place by the revolutionary councils, discuss the difficulties encountered in instituting these reforms, and analyze the reasons for their failure.